Influence of glucocorticoids on a time-of-day-dependent variation in intradermal reactivity to histamine in dogs. (August 2016) - Goto, Shun; Shimizu, Sunao; Watanabe, Miwa; Osada, Hironari; Sasaki, Kazuaki; Shimoda, Minoru; Nagai, Makoto; Shirai, Junsuke; Itoh, Hiroshi; Ohmori, Keitaro
Highlights: A daily variation in intradermal reactivity to histamine was detected in dogs. Administration of prednisolone or trilostane disrupted this variation. Reactivity to histamine was reduced after the injection of hydrocortisone. Glucocorticoids may regulate a daily variation in histamine-mediated reactions. Abstract: The objectives of this study were to determine daily variation in intradermal reactivity to histamine in dogs and to evaluate a potential influence of glucocorticoids on reactivity. Wheal sizes formed after intradermal injections of histamine were measured every 6 h during a single 24 h period in six healthy dogs. To determine whether glucocorticoids were implicated in daily variation, intradermal reactivity to histamine was evaluated at 9:00 h and at 21:00 h during a single day in dogs that received oral prednisolone (a synthetic glucocorticoid) or oral trilostane (an inhibitor of endogenous glucocorticoid synthesis). Finally, the time required for the histamine reaction to diminish after an intravenous injection of hydrocortisone was also assessed. A significant time-of-day-dependent variation in intradermal reactivity to histamine was detected in dogs, with a larger wheal size observed at 9:00 h than at 21:00 h. Administration of prednisolone or trilostane disrupted this variation. Intradermal reactivity to histamine was significantly reduced 6 h after an intravenous injection of hydrocortisone. These results suggest that glucocorticoid secretion from the adrenal glands could be involved in the regulation of daily variation in histamine-mediated reactions in dogs.